Geometric Structure, Electronic Structure, and Spin Transition of Fe2+ Spin-crossover Molecules - Thanh, Nguyen Van; Anh, Nguyen Thi Nguyet; Tuan, Nguyen Anh (Communications in Physics, 2013)
We present a density functional study on the geometric structure, electronic structureand spin transition of a series of Fe2+ spin-crossover molecules, i.e., [Fe(abpt)2(NCS)2] (1),[Fe(abpt)2(NCSe)2] (2), and [Fe(abpt)2(C(CN)3)2] (3) with abpt = 4-amino-3,5-bis(pyridin-2-yl)-1,2,4-triazole in order to shed light on more about the dynamics of the spin-crossover phenomenon.All results presented in this study were obtained by using the exchange correlation PBE functional.For better accuracy, the hexadecapolar expansion scheme is adopted for resolving the charge densityand Coulombic potential. Our calculated results demonstrate that the transition between the low-spin (LS) and high-spin (HS) states of these Fe2+ molecules is accompanied with redistributionof atomic charge and reformation of molecular orbitals. These cause dierences in the kineticenergy, the electrostatic energy as well as the total energy between the LS and HS states. TheLS state is advantage in the kinetic energy in comparison to the HS state, while the HS state isadvantage in the electrostatic energy. Moreover, the coulomb attraction energy between the Fe2+ion and its surrounding anionic ions plays a crucial role for spin crossover occurring.